Інноваційні технології соціально-психологічної підтримки школярів в умовах воєнного часу - Равлюк, Тетяна, Андрій Татарчук (My University, 2025)
The article highlights the use of innovative technologies in the social and psychological support of schoolchildren in wartime. The main directions of work of the psychological service in the education system of Ukraine in the 2024/2025 academic year are defined. The results of the "Future Index" study (2023) are described. Examples of innovative digital technologies for social and psychological support of schoolchildren are provided.
Keywords: social and psychological support, "Children's Well-being Index" study, innovative technologies